2005
DOI: 10.1111/j.1365-2486.2005.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Net ecosystem CO2 exchange in Mojave Desert shrublands during the eighth year of exposure to elevated CO2

Abstract: Arid ecosystems, which occupy about 35% of the Earth's terrestrial surface area, are believed to be among the most responsive to elevated [CO 2 ]. Net ecosystem CO 2 exchange (NEE) was measured in the eighth year of CO 2 enrichment at the Nevada Desert Free-Air CO 2 Enrichment (FACE) Facility between the months of December 2003-December 2004. On most dates mean daily NEE (24 h) (lmol CO 2 m À2 s À1 ) of ecosystems exposed to elevated atmospheric CO 2 were similar to those maintained at current ambient CO 2 le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 24 publications
10
98
1
3
Order By: Relevance
“…Phillips et al (2006) likely have the greatest contributions of roots to soil respiration. Thus, root respiration at the NDFF is unlikely the cause of increased soil or ecosystem respiration observed with elevated CO 2 (this report, Jasoni et al 2005). Contrary to the field results, L. tridentata root systems under elevated CO 2 were larger in 10-month old greenhouse seedlings (Table 7).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 99%
“…Phillips et al (2006) likely have the greatest contributions of roots to soil respiration. Thus, root respiration at the NDFF is unlikely the cause of increased soil or ecosystem respiration observed with elevated CO 2 (this report, Jasoni et al 2005). Contrary to the field results, L. tridentata root systems under elevated CO 2 were larger in 10-month old greenhouse seedlings (Table 7).…”
Section: The Nevada Desert Face Facilitymentioning
confidence: 99%
“…SIC in the top 60 cm of soil increased by 5079245(SD) g C/m 2 per year over the 7 years of grazing removal, which is equivalent to a rate of C increase in the plantÁ soil system of 3669229(SD) g C/m 2 per year. Other studies have reported high rates of C uptake: 102Á127 g C/m 2 per year in the Mojave Desert (Jasoni et al 2005;Wohlfahrt et al 2008) and 62Á622 g C/m 2 per year in saline/ alkaline desert soils in China (Xie et al 2009). However, these rates of C increase are unusually large compared with some other studies (29 g C/m 2 per year (Reeder et al 2004) and 0.12Á0.42 g C/m 2 per year (Schlesinger et al 2009)), which are comparable to the rates of C uptake in forests (Waring et al 1998).…”
Section: Grassland Restoration Following Grazer Removalmentioning
confidence: 99%
“…Only the data for the last 120 sec were used to calculate SCE as Eq. (1) (Jasoni et al, 2005;Chen et al, 2009):…”
Section: Measurement Of Sce and Soil Temperature And Moisturementioning
confidence: 99%